PERSEPSI MASYARAKAT TERHADAP FUNGSI RAWA DI DAERAH MUSI RAWAS - Septi Kurnia; Meli Astriani; Saleh Hidayat (UNIVERSITAS PGRI MADIUN, 2021)
Swamps are part of relatively flat land along the coast, streams or lakes and there is vegetation in the form of water plants, leading to the land up to ± 100 km which is generally affected by tides from the surrounding rivers. The method used in this study is a qualitative descriptive method, namely a method of analysis that seeks to explain the conditions of the object of study according to certain criteria so that it can provide a real picture of what is happening in the research place. Public Perception of Swamp Function in the Musi Rawas Area. People living in O. mangunharjo Village use swamps to help farmers in the use of conversion of agricultural land. However, to find out people's perceptions of the function of swamps, there are ten questions to analyze the community's perceptions of the function of swamps in the Musi Rawas area. From the research activities, it is known that from the community's perception of the function of swampland in O. Mangunharjo village, Musi Rawas Regency, there are many activities or activities that occur around swamps carried out by farmers such as; looking for grass for livestock, then hoeing or plowing the fields and farmers who plant vegetables considering that swamps are very important to the balance of the environment, especially in the economy of the people around O. Mangunharjo village in Musi Rawas Regency, there are 2 respondents who do not know the impact of the damage the swamp ecosystem affects the surrounding environment and 3 respondents know its impact. Based on PKL activities, it can be concluded that the community knows the function of swamps in the surrounding settlements, namely that the presence of swamps can balance the ecological functions of the environment.